2009
DOI: 10.1111/j.1540-6229.2009.00240.x
|View full text |Cite
|
Sign up to set email alerts
|

If You Promise to Build It, Will They Come? The Interaction between Local Economic Development Policy and the Real Estate Market: Evidence from Tax Increment Finance Districts

Abstract: The analysis in this article examines the impacts of one of the more prominent economic development tools, tax increment financing (TIF) districts, on the local commercial real estate market. The study area is the city of Chicago, a community with a long history of reliance on TIF districts as a means to foster local development initiatives. A treatment effects model is used to address the selection bias often attributed to studies of public policy impacts on real estate markets. The results indicate that comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…TIF districts that were found to have faster property value growth, on average, were industrial, were located closer to down-town Chicago, were lower-density, were more blighted, were larger, and had a higher proportion of white residents. Using propensity score matching to attempt to address the counterfactual, Smith (2009) found positive associations between TIF designation and commercial property values in Chicago between 1992 and 2000. Also focusing on Chicago over a similar time period (1993 to 1999), Weber, Bhatta, and Merriman (2003) examined industrial property values.…”
Section: A Property Valuesmentioning
confidence: 99%
“…TIF districts that were found to have faster property value growth, on average, were industrial, were located closer to down-town Chicago, were lower-density, were more blighted, were larger, and had a higher proportion of white residents. Using propensity score matching to attempt to address the counterfactual, Smith (2009) found positive associations between TIF designation and commercial property values in Chicago between 1992 and 2000. Also focusing on Chicago over a similar time period (1993 to 1999), Weber, Bhatta, and Merriman (2003) examined industrial property values.…”
Section: A Property Valuesmentioning
confidence: 99%
“…Studying Indiana, Man and Rosentraub (1998) found that residential property values were higher in TIF adopting cities than in those without TIF districts. Smith (2009) reports a similar effect in Chicago, with neighborhood quality influencing the magnitude of the impacts on commercial property values. His study evaluated the effect on TIF across a number of stated goals, such as blight reduction.…”
Section: Tif and Economic Activitymentioning
confidence: 83%
“…In a study of Milwaukee TIF districts, Carroll (2008) found that the growth of business property value within the TIF district is attributable to the capitalization of higher quality public services offered in these districts. Smith (2009) reports a similar effect in Chicago, with neighborhood quality influencing the magnitude of the impacts on commercial property values. Byrne (2006) found that property value growth tends to be higher in Chicago TIFs than the municipality as a whole and that larger TIF districts, those close to the city center, TIFs with a higher proportion of white residents and those located in low-density areas experience higher growth.…”
Section: Tif and Economic Activitymentioning
confidence: 83%
“…A high percentage of future population growth and housing need in cities can be covered through using abandoned land in down town, having a balanced density, regeneration, renovation and reconstruction of worn out texture and old buildings (Grenadier, 1996;Newell, 2010). Infill city development have the role of neighborhood revitalizer, health and safety risks reducer of worn out textures (Weber et al, 2003;Smith, 2006;Weber et al, 2007;Smith, 2009). United States and Europe were the first ones who applied infill city development policy in 1980 (Cheng et al, 2009) in a way that it is the heart of urban land policies in Europe.…”
Section: Infill City Developmentmentioning
confidence: 99%